Effect of cogging torque minimization techniques on performance of an axial flux permanent magnet machine - Kumar P.; Reza M.M.; Srivastava R.K. (My University, 2025)
Numerous techniques have been proposed till now for the reduction of cogging torque in a permanent magnet machine. Most of these techniques are mainly based on design modification of various machine parts such as tooth, slot or PM shape. However, the influence of these design modifications on the performance parameters of the machine have not been studied yet. This paper compares a few cogging torque reduction techniques taking into account the amount of cogging reduction achieved by each method. Their effect on various performance parameters of the machine such as magnetic flux density distribution in air gap, per phase induced emf and their harmonic analysis are also analyzed. The various analysis results have been obtained using Finite Element Method (FEM) based simulations. © 2017 IEEE.